AN EFFECTIVE THICKNESS PROPOSAL FOR STRENGTH EVALUATION OF ONE-SIDE PITTED STEEL PLATES UNDER UNIAXIAL COMPRESSION - NOURI, ZORAREH HADJ MOHAMMAD ESMAEIL (2012)
THIS PAPER PRESENTS THE RESULTS OF AN INVESTIGATION INTO THE POST-BUCKLING BEHAVIOUR AND ULTIMATE STRENGTH OF IMPERFECT PITTED STEEL PLATES USED IN SHIP AND OTHER MARINE-RELATED STRUCTURES. A SERIES OF ELASTIC-PLASTIC LARGE DEFLECTION FINITE ELEMENT ANALYSES IS PERFORMED ON PITTED STEEL PLATES. THE EFFECTS OF PITTING CORROSION ON ONE SIDE OF THE PLATES ARE INTRODUCED INTO THE FINITE ELEMENT MODELS. THE EFFECTS ON PLATE COMPRESSIVE STRENGTH AS A RESULT OF PARAMETRIC VARIATION OF THE PITTING CORROSION GEOMETRY ARE EVALUATED. A PROPOSAL ON THE EFFECTIVE THICKNESS IS CONCLUDED IN ORDER TO ESTIMATE THE ULTIMATE STRENGTH AND EXPLORE THE POST-BUCKLING BEHAVIOUR OF PITTED STEEL PLATES UNDER UNIAXIAL COMPRESSION.